Sexual dimorphism of Liolaemus cuyanus Cei & Scolaro, 1980 (Iguania: Liolaemidae) in a population of San Juan, Argentina - Laspiur, Alejandro (2007)
The study of sexual dimorphism can offer answers about the biological meaning that implies the morphological differentiation between males and females. However, these differences can be consistently explained knowing that exist selective pressures that infl uences on degree of sexual dimorphism in the species. For these reasons, we study the sexual dimorphism in a population of Liolaemus cuyanus of San Juan’s Monte.We measure 12 morphometric variables in 51 females 43 males. Of these, eight were signifi cantly bigger in the males: the snout-vent length, the width, the length and the high of head, the interocular distance, femur’s length, tibio-fi bula’s length and the tail’s length. The distance of separation between limbs was signifi cant bigger in the females. It is explained and compare the obtained results with dimorphisms found in other species of the genus.